Guilt, tears and burnout—Impact of UK care home restrictions on the mental well‐being of staff, families and residents. (21st February 2022) - Giebel, Clarissa; Hanna, Kerry; Marlow, Paul; Cannon, Jacqueline; Tetlow, Hilary; Shenton, Justine; Faulkner, Thomas; Rajagopal, Manoj; Mason, Stephen; Gabbay, Mark
Abstract: Aims: The aim of this study was to explore the impact of the pandemic on the emotional and mental well‐being of family carers, care home staff and residents, in light of changing restrictions, increased testing and vaccination rollout in the UK. Design: Longitudinal, qualitative semi‐structured interview study. Methods: Remote semi‐structured interviews were conducted with family carers of care home residents with dementia and care home staff from different care homes across the UK. Baseline and follow‐up interviews were conducted in October/November 2020 and March 2021, respectively. Data were analysed using inductive thematic analysis involving members of the public with caring experiences. Results: In all, 42 family carers and care home staff participated at baseline, with 20 family carers and staff followed up. We identified four themes: (1) Developing anger and frustration; (2) Impact on relationships; (3) Stress and burnout; and (4) Behavioural changes, and perceived impact on residents. The mental health of everyone involved, including family carers, care home staff and residents, has been negatively affected, and relationships between family carers and staff have been severely strained. There was a general lack of adequate mental health support, with little relief. Conclusions: The pandemic has had a detrimental impact on the lives of those surrounding care homes—from residents and staff to family carers. Consideration should be given on how to best support the mental health needs of all three groups, by providing adequate easily accessible mental health care for all. This should also focus on rebuilding the relationships between family carers and care home staff. Impact: This is the first paper to highlight the effects of the long‐lasting and miscommunicated restrictions on residents, carers and care home staff, and highlight the urgent need for continued mental health support.